2012
DOI: 10.1007/s11604-012-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung-cancer related chest events detected by periodical follow-up CT after stereotactic body radiotherapy for stage I primary lung cancer: retrospective analysis of incidence of lung-cancer related chest events and outcomes of salvage treatment

Abstract: Post-SBRT lung-cancer related chest events (as detected by periodical chest CT) were not uncommon (approximately 40 % at 3 years from SBRT), and it was possible to treat more than half of these lesions with curative-intent salvage treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Salvage surgery after SABR appears to be safe: at least four small studies have reported on patients who have undergone surgery for salvage of a post-SABR recurrence. [69][70][71][72] Across these four studies, such surgery is generally well tolerated with a favorable toxicity profile, with only one patient sustaining a major toxicity (fistula requiring further surgery for correction). 71 Salvage repeat irradiation in the setting of SABR has shown good outcomes in terms of local control, and overall survival, although toxicity is likely higher, as described above.…”
Section: General Follow-up Recommendationsmentioning
confidence: 99%
“…Salvage surgery after SABR appears to be safe: at least four small studies have reported on patients who have undergone surgery for salvage of a post-SABR recurrence. [69][70][71][72] Across these four studies, such surgery is generally well tolerated with a favorable toxicity profile, with only one patient sustaining a major toxicity (fistula requiring further surgery for correction). 71 Salvage repeat irradiation in the setting of SABR has shown good outcomes in terms of local control, and overall survival, although toxicity is likely higher, as described above.…”
Section: General Follow-up Recommendationsmentioning
confidence: 99%
“…Five were treated with salvage SBRT and two with salvage surgery. Those that received curative intent salvage therapy of either modality had a significantly better 1-year overall survival (OS) of 86% compared to a 1-year OS of 40% for those that did not (P=0.0289) (8). In another investigation, Brooks et al retrospectively examined the charts of 912 T1N0 NSCLC patients salvaged by surgery or reirradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers evaluated patterns of failure after SBRT for early-stage NSCLC and the application rate of salvage treatment to patients with isolated local or regional tumor recurrence. 13 , 14 Hamamoto et al 13 administered SBRT to 86 patients with stage I NSCLC between 2006 and 2009. With a median follow-up period of 26 months, 10 (11.6%) local failures and 3 (3.5%) regional lymph-node failures were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers evaluated patterns of failure after SBRT for earlystage NSCLC and the application rate of salvage treatment to patients with isolated local or regional tumor recurrence. 13,14 Hamamoto et al 13 Four papers retrospectively investigated efficacy and safety of salvage RT for local tumor recurrence in patients who had received prior definitive SBRT for primary lung cancer or metastatic lung tumors [15][16][17][18] (Table 2). Peulen et al 15 from Karolinska University Hospital published the first report on salvage SBRT for local recurrence after previous SBRT.…”
Section: Salvage Rt For Local Tumor Recurrencementioning
confidence: 99%
See 1 more Smart Citation